Hábitos de leitura e escrita : impacto sociocultural em cognição com ênfase em funções executivas - Salem, Andressa Aparecida Garces Gamarra (2021)
Sociocultural variables can positively influence cognitive development. However, reading and writing habits have received less attention in the investigation of their relationship with cognitive and executive functions throughout development, still very incipient in adolescence. Thus, these factors need to be better explored in order to clarify their contributions, for more accurate clinical and school evaluations and for the promotion of strategies for sociocultural neuropsychological interventions. Thus, this master's thesis was carried out from two studies. The first aimed to map the sociocultural variable reading and writing habits regarding its operationalization and characterization of the impact on cognition, more specifically in EFs, in different age groups of development. For this study, a systematic review of the literature was conducted using the PRISMA method. The final sample consisted of 49 empirical articles with a predominance of studies with children and adults and the elderly, a variability in the measurement of reading and writing habits in different age groups and positive impacts of this variable in different executive and cognitive domains, mainly in language, academic readiness and executive functions, both in healthy and clinical populations. The second study aimed to investigate the impact of the frequency of reading and writing habits (FRWH) of healthy adolescents on tasks of executive functions, intelligence and learning. In this empirical study, 47 healthy adolescents, aged between 12 years and 17 years and 11 months, from public and private schools participated, who underwent a neuropsychological evaluation. To compare scores in neuropsychological tests between high and low FRWH groups, a Student's T Test was performed. For the comparison of the distribution for sociodemographic variables, OneWay ANOVA analyses were performed and for categorical analyses between groups, Chi-square was conducted. Adolescents with higher FRWH performed better in EF tasks (semantic verbal fluency, second DNO title, errors in the FDT count), intelligence (vocabulary) and learning (correct answers, time and efficiency in aritmetics). It is also note point that adolescents with higher FHLE have parents who write more frequently. The FHLE factor as well as its quality should be part of neuropsychological research in clinical and research, as a variable that can lead to false negative, if very high, or false positive, if very low. Additionally, in neuropsychological intervention programs, the promotion of reading and writing habits can be an early-preventive strategy for different age groups and in different contexts, such as clinicians and areas of education, health and social assistance.